2005
DOI: 10.1016/j.febslet.2005.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of stefin B‐deficient thymocytes towards staurosporin‐induced apoptosis is independent of cysteine cathepsins

Abstract: Stefin B (cystatin B) is an inhibitor of lysosomal cysteine cathepsins and does not inhibit cathepsin D, E (aspartic) or cathepsin G (serine) proteinases. In this study, we have investigated apoptosis triggered by camptothecin, staurosporin (STS), and anti-CD95 monoclonal antibody in the thymocytes from the stefin B-deficient mice and wild-type mice. We have observed increased sensibility to STS-induced apoptosis in the thymocytes of stefin B-deficient mice. Pretreatment of cells with pan-caspase inhibitor z-V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…A431 cells were infected with wt MS11 or MS11pilT or mock infected. Parallel uninfected cultures were treated with STS as a positive control for apoptosis (5,22). The cells were stained with YO-PRO-1 and PI and analyzed by flow cytometry (18).…”
Section: Resultsmentioning
confidence: 99%
“…A431 cells were infected with wt MS11 or MS11pilT or mock infected. Parallel uninfected cultures were treated with STS as a positive control for apoptosis (5,22). The cells were stained with YO-PRO-1 and PI and analyzed by flow cytometry (18).…”
Section: Resultsmentioning
confidence: 99%
“…The protein concentration of the cell lysates was measured using the Bradford reagent (Bio-Rad). The lysates were subjected to electrophoresis on 12.5% SDS-polyacrylamide gels followed by Western blotting as described previously (33). The proteins were visualized with ECL (Amersham Biosciences) according to the manufacturer's instructions.…”
Section: Cell Lysate Preparation and Western Blot Analysismentioning
confidence: 99%
“…Monolayer BMDMs at 80% confluence were first washed with ice-cold PBS, followed by the direct addition of the radioimmune precipitation assay lysis buffer supplemented with the Complete protease inhibitor mixture (Sigma) Cell lysates were prepared as described previously (33). The protein concentration of the cell lysates was measured using the Bradford reagent (Bio-Rad).…”
Section: Cell Lysate Preparation and Western Blot Analysismentioning
confidence: 99%
“…The lysates were then clarified by centrifugation at 13 000Âg for 10 min at 4°C, and the protein concentrations of the cell lysates were measured using the Bradford reagent (BioRad). The lysates were subjected to electrophoresis on 12.5% SDS-PAGE gels followed by Western blotting as described previously [8]. The proteins were visualized with ECL (GE Healthcare) according to the manufacturer's instructions.…”
Section: Whole Cell Lysates Preparation and Western Blot Analysismentioning
confidence: 99%
“…Studies of stefin B-deficient mice show that lack of this inhibitor is associated with the signs of cerebellar granular cell apoptosis, progressive ataxia and myoclonic seizures [6]. It was demonstrated that stefin B deficiency sensitizes the cells to the oxidative stress-induced cell death [7,8]. In the past, several studies examined the influence of cystatins on nitric oxide (NO) and cytokine synthesis, predominantly type II cystatins induce NO secretion in IFN-c-primed mouse macrophages [9,10].…”
Section: Introductionmentioning
confidence: 99%